El Excentrico, 1978-03-05 - Garcia, Bert:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2024)
March 5, 1978 [5 de marzo de 1978]. Ano 28, No 23. Cover contains several portraits of the contestants of the March 1978 Queen and Coronation Ball, hosted by the San Jose Chapter of the American GI Forum. The event would take place on March 18th, 1978 at the Campbell Pavilion in the Santa Clara County Fairgrounds.